Transfusion practices in obstetrics and gynaecology in a tertiary care center - Singh, Shashi; Sinha, Parul; Yadav, Gunjan; Gupta, Uma; Tyagi, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was an effort to identify and highlight existing transfusion practices in our hospital, including the indications of various blood components used and the allergic reaction encountered. Obstetric hemorrhage remains major cause of maternal mortality worldwide and Blood transfusion can be a lifesaving intervention. Methods: This was a prospective cross- sectional study conducted on 172 patients who underwent blood and blood component transfusion. Hb concentration <7g/dL was determined to be an indication for blood product transfusion. Results: In this study the most common indication for blood transfusion was antenatal patient with anemia (32.8%) followed by ruptured ectopic pregnancy (19.5%) and postpartum hemorrhage (18.8%). Amongst gynecological patients, the most common cause for transfusion was abnormal uterine bleeding (AUB) (61.4%). Majority patients were given single unit transfusion. Adverse reactions found in our study were not statistically significant. Conclusions: Therefore this study concludes that we still need to go a long way in order to train the medical fraternity at all levels to learn to identify the valid indications for transfusion and select appropriate component for management.